The factors that affectings job satisfaction among employees at RP Chemicals (Malaysia) Sdn. Bhd. / Noor Adillah Rahim - Rahim, Noor Adillah (2017)
The purpose of this study is to find out the most important factors that affecting job satisfaction and the relationship between element factors towards job satisfaction. Specifically, the researcher took Working conditions, pay & promotion, and supervision as the antecedents to see their impact on job satisfaction. This can help us to better understand about the satisfaction level of employees and how we can motivate employees to perform their job efficiently and effectively. The sample consists of 50 respondents, who were selected using convenience sampling. The questionnaire was distributed among 50 respondents in RPCM. The data analyzed using SPSS Version 21.0 and the results were presented by figures and tables. The findings for this study can improve the productivity and job performance of employee in the organization.